GOVERNMENT POLICY ANALYSIS OF PLASMA INDUSTRIAL DISTRICT PURBALINGGA HAIR AND EYELASH FALSE IN THE DISTRICT PURBALINGGA CASE STUDY OF SUBDISTRICT PENGADEGAN IN 2005-2015 - Galuh Diptya Kartikasari; Purwoko .; Sulistyowati . (Journal of Politic and Government Studies, 2016)
ABSTRACTAnalysis of government policies Purbalingga it on the plasma industry hair and falseeyelashes Purbalingga case studies Subdistrict Pengadegan in 2005-2015 has the aim to find outwhy the selected pattern hair industry plasma and false eyelashes in Purbalingga, knowing howto develop the plasma industry and knowing how the plasma acts as a forum for communityempowerment.Methods in this research use qualitative research with the main data types are the wordsand actions. Sources of data obtained derived from primary and secondary data. To search forinformants in this study is conducted with a purposive sample (making intentional) and snowballsampling (sampling through the help of key informants to identify the source of the nextinformant who is still involved in the research). Techniques for collecting data later usinginterviews, observation and documents.Interim findings in this study is nothing law that regulates the implementation of industrialplasma hair and false eyelashes. The condition causes there are two patterns in theimplementation of plasma in the Subdistrict Pengadegan. The second pattern is the pattern ofsuch branches and collector pattern. There is a loss and the benefits derived from the twopatterns.The results of this study are expected later can be beneficial for the government as a policyevaluation, for the people especially those plasma workers to be motivated establish industrialenterprises hair and false eyelashes.Keywords: Government Policy, Plasma Hair and Eyelashes